Community participation in education : does decentralisation matter? An Indonesian case study of parental participation in school management : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Development Studies at Massey University, Palmerston North, New Zealand - Fitriah, Amaliah (Massey University, 2010)
A prominent idea in the decentralisation and development literature is that decentralisation leads to deeper and stronger community participation. This thesis seeks to examine this argument by investigating the practice of community participation in the Indonesian decentralisation context, focusing on parental participation through access to and control over school financial resources. Drawing on a case study in Depok city, the practice of parental involvement has been explored by identifying the characteristics and the extent of parents’ participation in school management. School Committees (SCs), as a mechanism of community involvement provided by the decentralised education policy, were also examined in this research to develop an understanding of parental representation in school management. The study found that the characteristics and the extent of parents’ participation in school management have changed and decreased significantly as a result of a new Free School Programme (FSP) introduced by the government in 2009 which freed parents from school operational cost. Prior to FSP, parents actively participated in terms of supplying resources and involvement in school meetings, had some access to financial information, and had limited engagement with school budgeting through representation in SCs. However, the new absence of financial contribution by parents has affected parental participation by transforming it into a weaker form of participation where parents act as mere beneficiaries. The study also revealed that in the Indonesian context, the SCs, as institutional channels for community involvement in education provided by the education decentralisation policy, are not effective in terms of representing and engaging parents in school management. Based on the evidence above, this thesis concluded that in the context of the Indonesian education system, decentralisation has not necessarily enhanced community participation. In this respect, decentralisation is not the only possible answer for achieving a meaningful and empowering parental participation in education. Furthermore, other contextual factors surrounding participation also have to be taken into account. While FSP brings the benefit of allowing students to access education freely, the absence of parental financial contribution has been proved to impact parental participation in a way that is contradictory to one of the purposes of decentralisation policy, which is to engage the community in educational management.
Keywords: School management; Free School Programme, Indonesia; Educational decentralisation; Indonesian education system; Fields of Research::330000 Education::330100 Education Studies::330104 Educational policy, administration and management